Agent-based dynamic spectrum trading algorithm in cognitive radio network - Shi-bing ZHANG; Guo-dong ZHANG; Zhi-hua BAO (Tongxin xuebao)
In order to improve the benefits generated by spectrum sharing, the spectrum management was studied and the agent-based dynamic spectrum trading algorithm was proposed. In the algorithm, the agent was used as a medium for spectrum trading, which reduced the huge system overhead among multi-primary service providers (PSP) and mul-ti-secondary users (SU). All PSP competed or cooperated with each other to achieve the maximum self-profit or total profit respectively, and come to terms with the agents on the final transaction price and quantity of spectrum. And then, the agent auctioned the spectrum among all SU. Each SU submitted a bid to the agent, then the agent allocated corres-ponding spectrum quantity to the SU. All SU adaptively adjusted the bids to achieve the maximum self-profit. Nash equi-librium was considered as the solution to both the game among PSP and the auction among SU. Simulation results show that the proposed algorithm performs well.